Comparison between behavioral thresholds and brain-stem evoked response audiometric thresholds - MANOJ KUMAR (Journal of All India Institute of Speech and Hearing, 1970)
The present study was done with an aim to establish the relationship between behavioral thresholds and ABR thresholds, using 10 normal and 10 pathological subjects.